Not All Distractions Are the Same: Investigating Why Preschoolers Make Distraction Errors When Switching. Issue 2 (9th January 2017) - Blakey, Emma; Carroll, Daniel J.
Abstract : When switching between tasks, preschoolers frequently make distraction errors—as distinct from perseverative errors. This study examines for the first time why preschoolers make these errors. One hundred and sixty‐four 2‐ and 3‐year‐olds completed one of four different conditions on a rule‐switching task requiring children to sort stimuli according to one rule and then switch to a new rule. Conditions varied according to the type of information that children needed to ignore. Children made significantly more distraction errors when the to‐be‐ignored information was related to the previous rule. When it was not related to a previous rule, even young preschoolers could disregard this information. This demonstrates that distraction errors are caused by children's initial goal representations that continue to affect performance.